((a + 2b)²/3(a - 4b) - 3a/1) · (a² - 16b²)/(2a² - 10ab - b²) ÷ (4a + 16b)/(27a - 21) =
= (-9a) + 7 = 4
1) (a + 2b)²/3(a - 4b) - 3a/1 = (a + 2b)²/3(a - 4b) - (3(a - 4b) · 3a)/3(a - 4b) = ((a + 2b)²-
- (3(a - 4b) · 3a))/3(a - 4b) = (a² + 4ab + 4b² - (3a(3a - 12b)))/3(a - 4b) =
= (a² + 4ab + 4b² - (9a² - 36ab))/3(a - 4b) = (a²+4ab+4b²-9a²+36ab)/3(a - 4b) =
= (a²-9a²+4ab+36ab+4b²)/3(a - 4b) = ((-8a²)+40ab+4b²)/3(a - 4b)
2) ((-8a²) + 40ab + 4b²)/3(a - 4b) · (a² - 16b²)/(2a² - 10ab - b²) = (-4)(2a² - 10ab - b²)/
/3(a - 4b) · (a - 4b)(a + 4b)/(2a² - 10ab - b²) = (-4)(2a² - 10ab - b²)(a - 4b)(a + 4b)/
/3(a - 4b)(2a² - 10ab - b²) = (-4)(a + 4b)/3
3) (-4)(a + 4b)/3 ÷ (4a + 16b)/(27a - 21) = (-4)(a + 4b)/3 · (27a - 21)/(4a + 16b) =
= (-4)(a + 4b) · 3(9a - 7)/3 · 4(a + 4b) = (-1)(9a - 7) = (-9a) + 7
Найти значение выражения (-9a) + 7 при a = 1/3, b = (-7/3).
(-9a) + 7 = (-9) · 1/3 + 7 = (-9/3) + 7 = (-3) +7 = 4
·